La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Journeys of Attachments, Trajectories of (Mis)fitting: Musicking in Deaf Communities in Montreal - Grenier, Line; Leduc, Véro (Troubling Inheritances: Memory, Music, and Aging, 2022)
This book provides an interdisciplinary focus on music, memory, and ageing by examining how they intersect outside of a formal therapeutic context or framework and by offering a counter-narrative to age as decline. It contributes to the development of qualitative research methodologies by utilizing and reflecting on methods for studying music, memory, and ageing across diverse and interconnected contexts. Using the notion of inheritance to trouble its core themes of music, memory, ageing, and methodology, it examines different ways in which the concept of inheritance is understood but also how it commonly refers to the practice of passing on, and the connections this establishes across time and space. It confronts the ageist discourses that associate popular music predominantly with youth and that focus narrowly, and almost exclusively, on music's therapeutic function for older adults. By presenting research which examines various intersections of music and ageing outside of a therapeutic context or framework, the book brings a much-needed intervention.

Nos mains qui vibrent – Un texte à huit mains sur une recherche-création en musiques sourdes - Leduc, Véro; Saunders, Daz; Youssouf, Hodan; Witcher, Pamela (Canadian Journal of Disability Studies, 2021)
“Deaf music?” Faced with this question, many people think about the attempts to give Deaf people "access" to music, used here in its normative hearing form (eg a musical soundtrack). Translation of vocal songs in various sign languages, transformation of sound tracks into vibratory experience, musical rhythms broadcast by visual speakers... accessibility initiatives are numerous, but more often than not unidirectional: they aim to make hearing music accessible to Deaf people, reputed to live in a "world of silence". Our vibrant hands aim to deconstruct this concept of accessibility: what if hearing people had access to signed music? You can’t sign? Enjoy these creation by letting yourself be captivated by the vibrations. Inspired by the Deaf artist Christine Sun Kim who reclaims sound, Our vibrant hands is a research-creation carried out thanks to the collaboration of four Quebec Deaf artists of various origins. Four workshops held in 2018 allowed us to explore signed music, using (Quebec and American) sign languages, gestures and vibrations. Screened for the first time at the VIBE symposium: Challenging ableism and audism through the arts, it is here the subject of an eight- handed reflexion, produced in 2019. What attachment do we have with music? How is signed music different from hearing music? What does it mean for us to deconstruct audism in music? These are the questions that guided this multilingual exchange in Quebec sign language, French and English.
Number: 2